Discourses on women and female suffrage in the press of la Araucanía (Chile, 1935-1952) (Anclajes, 2023)
This article focuses on the social imaginary about women in the discourse of El Diario Austral de Temuco, a publication from Chile’s Araucanía region, during the enactment of women's suffrage in the country (1935-1952). Following Potter’s model of discourse analysis, the article examines the socio-imaginary constructions articulated in the factual accounts that circulated in the public arena of the local press. We find that this social imaginary was constructed along two central discursive axes: the domesticity of political participation, and the legitimacy of women's suffrage as grounded on their political contributions through the essential nature of their femininity.
Keywords: Female Suffrage; Discourse; Press; Social Imaginaries; Araucanía